The Specificity of Justice System in Countering Corruption Crimes in Algerian Legislation - Guerroudj, Raouf; Bachir, Radhia (مجلة الباحث للدراسات الأكاديمية, 2022)
The present study aims to identify the role of the judicial system in the fight against corruption crimes in the Algerian legislation, with new mechanisms that the legislator has created that are compatible with the progress that have touched various fields, especially since this crime is witnessing a perceptible and alarming spread at the international and national levels. This study was mainly based on analytical approach to analyze the various legal texts related to this matter.